The Impact Of Inflation, US Dollar Exchange Rate And Land Transportation Freight Towards Non-Oil And Natural Gas Export To America, Japan, Australia And England Through Surabaya Port In The Year Of 2015-2017 - Sembiring, Murpin Josua; Sasono, Herman Budi (Archives of Business Research, 2019)
Indonesia is one of the countries which frequently administer both export and import activities with many countries in the world. Export activities done by Indonesia are influenced by non-oil and natural gas export. This research analyses the impact of inflation, US Dollar exchange rate, and land transportation freight towards non-oil and natural gas export activities to America, Japan, Australia, and England through Surabaya Port in the year of 2015 to 2017. Furthermore, this research uses quantitative method and the data collected are gathered from secondary. The data analysis used in this research is multiple linear regressions. The result of this research shows that all independent variables which are inflation (X1), US Dollar exchange rate (X2), and land transportation freight (X3) bring non-significant impact towards non-oil and natural gas export to four countries mentioned before. However, in the non-oil and natural gas export activities to Australia, the US Dollar exchange rate variable (X2) brings significant impact. Meanwhile, land transportation freight variable (X3) is significant towards the export activities to England.